Characterization and spoilage potential of Bacillus cereus isolated from farm environment and raw milk - Meng, Lu; Zhang, Ruirui; Dong, Lei; Hu, Haiyan; Liu, Huimin; Zheng, Nan; Wang, Jiaqi; Cheng, Jianbo (Frontiers in Microbiology, 2022)
Bacillus cereus sensu lato (B. cereus sl) is important spoilage bacteria causing milk structure and flavors changes and is ubiquitous in the environment. This study addresses the biodiversity, toxicity and proteolytic activity of B. cereus sl from 82 environmental samples and 18 raw bovine milk samples from a dairy farm in the region of Tianjin. In sum of 47 B. cereus sl were characterized through biochemical tests, 16S rRNA gene sequencing, and panC gene analyses. Fourteen sequence types (STs) of B. cereus sl were found in raw bovine milk samples, with five new STs (ST2749, ST2750, ST2751, ST2752, and ST2753) were identified in this study. ST1150 was the dominant ST, associated with fecal, air, drinking water, teat skin, teat cup, and teat dip cup. The results of toxin gene analyses showed that 12.77% and 8.51% isolates carried hblACD and nheABC operons. In addition, the detection rate of emetic cesB genes were 21.28%. B. cereus sl demonstrated high spoilage potentials even at 7℃, which has the proteolytic activity of 14.32±1.96 μmol of glycine equivalents per mL. Proteolytic activities were significantly (p＜0.05) decreased after the heat treatment. The residual activity of protease produced at 7℃ were significantly higher than that produced at 25℃ and 37℃ after treatment at 121°C 10 s and 135°C 5s (p＜0.01). Together, the results provide insights about the characteristics of B. cereus sl from farm environment and raw bovine milk, and revealed that B. cereus sl contamination should also be monitored in raw milk for UHT products. This knowledge illustrates that strict cleaning management should be implemented to control B. cereus sl and assure high quality milk products.